Analysis of Ritual Communication in The Timbung Pejanggik War Tradition: A Symbolic Interactionism Perspective - Husnul Khotimah; Ishanan Ishanan; Suhadah Suhadah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This study examines the symbolic meaning and cultural communication practices in the Timbung war ritual tradition in Pejanggik, Central Lombok. This tradition, rooted in historical values and ancestral heritage, is an important part of social identity, religious values, and community harmony. This study aims to analyze the symbolic interaction, function, and meaning contained in each element of the ritual through a symbolic interactionism approach. The method used is qualitative with data collection through semi-structured interviews with traditional leaders, religious leaders, the community, and cultural actors. The results of the study show that the Timbung War functions as a communication ritual that strengthens social cohesion, preserves ancestral values, and integrates Islamic teachings through prayer and togetherness. Each symbol in the ritual, such as bamboo, water, offerings, and coordinated movements, contains meanings of purity, unity, protection, and respect for ancestors. The study concludes that the Timbung War is a cultural tradition that remains alive and preserved through regeneration and the active role of the community amid the tide of modernization. The findings of this study contribute to efforts to preserve local culture, strengthen community identity, and can be used as a reference in the development of cultural education programs and tradition preservation policies based on community participation.